(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
The responsibility to protect emerged as a concept, an idea-force of contemporary society in response to the proliferation of new conflicts and threats that transcend borders and are characterised by massive human rights violations. A fundamental way to achieve this protection is for states to introduce national laws against war crimes, genocide and crimes against humanity in order to prevent judicial or criminal impunity, given that the court cannot punish the culprits unless such legislation exists.